Clinical Utility of Weekly Laboratory Testing in the Outpatient Management of Preeclampsia and Gestational Hypertension - Morgan, John A.; McCalmont, Lauren E.; Towers, Craig V.; Davis, Melissa; Hankins, Miriam; Rangnekar, Niyati; McNeal, Mary Ellen; Lewis, David F. (American Journal of Perinatology Reports, 2020)
Objective To investigate the utility of obtaining weekly laboratory testing in patients managed as an outpatient for gestational hypertension and preeclampsia without severe features.Study Design A multisite retrospective cohort study was performed evaluating preterm women diagnosed with gestational hypertension/preeclampsia managed in an outpatient setting between gestational ages of 230/7 and 366/7. Patients were divided into two groups: weekly laboratory evaluation (laboratories group) and a no laboratories group. The primary study outcome was composite maternal morbidity including more than one of the following: development of severe features, HELLP syndrome, eclampsia, placental abruption, maternal intensive care unit admission, or maternal death.Results A total of 204 patients were included in this study, laboratories group (n = 120) and no laboratories group (n = 84). The laboratories group was older (28.8 vs. 26.6 years, p = 0.02), had a higher rate of chronic hypertension (44 [36.7%] vs. 17 [20.2%], p = 0.01), and more often experienced the primary composite outcome (53 [44.2%] vs. 24 [28.5%], p = 0.02). No patients in our cohort were delivered for abnormal laboratory values.Conclusion This study found that weekly laboratory testing may have minimal clinical utility in the outpatient management protocol in monitoring patients with mild gestational hypertension or preeclampsia. Delivery was guided by other clinical factors.
Keywords: mild preeclampsia; preeclampsia without severe features; gestational hypertension; chronic hypertension in pregnancy; superimposed preeclampsia; liver enzymes; platelet count; preeclampsia with severe features